Effect of Different Floor Space Allowances on Body Weight Changes, Voluntary Feed, Nutrients, and Water Intake in Indigenous Sheep - Khimani, Sagar S; Patel, Yogesh G; Modi, Rakesh J; Trivedi, Manoj M (Indian Journal of Veterinary Sciences and Biotechnology, 2023)
Present study was conducted on 45 adult dry non-pregnant (25-30 kg) farm born indigenous ewes. The animals were divided into three treatment groups, i.e., T1: 1.5 m2 (4 animals in each pen), T2: 1.25 m2 (5 animals in each pen) and T3: 1.0 m2 (6 animals in each pen) floor space allowances with three replications in each treatment. The animals were maintained on farm feeding for 42 days of experiment with 15 days of adaptation period. The body weight of experimental animals was not influenced significantly (p<0.05) by different treatment groups, indicating that the floor space of 1.5, 1.25 and 1.0 m2 did not affect body weight of ewes. The DMI in term of g/d, was significantly (p<0.05) lower by 2.38 and 1.51 % in T2 and T1 compared to T3. DCP intake (g/d) was reduced by 1.66 and 1.05 % in T2 and T1 compared to T3, while TDN intake (g/d) was reduced by 2.22 and 1.42 % in T2 and T1 compared to T3 group, respectively. Contrary to this, reduction in water intake (l/d) was observed by 11.6 and 16.0 % in T2 and T3 compared to T1.